A Systematic Review on the Occurrence of Babesia spp. and Anaplasma spp. in Ticks and Wild Boar from Europe—A 15-Year Retrospective Study - Ioan Cristian Dreghiciu; Diana Hoffman; Tiana Florea; Ion Oprescu; Simona Dumitru; Mirela Imre; Vlad Iorgoni; Anamaria Plesko; Sorin Morariu; Marius Stelian Ilie (Pathogens)
The wild boar (Sus scrofa) has experienced significant population growth as well as geographic expansion across Europe over the past 15 years, leading to increased concerns regarding its role in the transmission of zoonotic pathogens. Among these, Babesia spp. and Anaplasma spp. are of particular importance due to their impact on both wildlife and domestic animals. This study systematically reviews the prevalence and distribution of Babesia and Anaplasma spp. in wild boars and associated tick vectors across multiple European countries, synthesizing data from literature published between 2010 and 2024. A comprehensive search of Scopus, Google Scholar, and PubMed databases was conducted using predefined keywords related to babesiosis, anaplasmosis, wild boars, Europe, and tick-borne diseases. A total of 281 studies were initially retrieved, of which 19 met the inclusion criteria following relevance assessment. Data extraction focused on pathogen identification, diagnostic methods, sample type, host species, and prevalence rates. Molecular detection methods, primarily PCR and sequencing, were the most used diagnostic tools. Results indicate substantial regional variations in the prevalence of Babesia and Anaplasma spp. A. phagocytophilum was detected in wild boar populations across multiple countries, with the highest prevalence rates observed in Slovakia (28.2%) and Poland (20.34%). Conversely, lower prevalence rates were recorded in France (2%) and Portugal (3.1%). Babesia spp. showed higher prevalence rates in Italy (6.2%), while its detection in other regions such as Romania and Spain was minimal or absent. Notably, spleen and multi-organ samples (spleen/liver/kidney) exhibited higher positivity rates compared to blood samples, suggesting an organotropic localization of these pathogens. The findings underscore the role of wild boars as reservoirs for tick-borne pathogens and highlight their potential to contribute to the epidemiological cycle of these infections. The increasing distribution of wild boars, coupled with climate-driven shifts in tick populations, may further facilitate pathogen transmission. Future studies should focus on integrating molecular, serological, and ecological approaches to improve surveillance and risk assessment. Standardized methodologies across different regions will be essential in enhancing comparative epidemiological insights and informing targeted disease management strategies.